Regioquímica das reações de ciclocondensação de azido vinilésteres na síntese de pirrolo[3,4-d]piridazinonas e pirróis ferrocenil substituídos - Libero, Francieli Maria (2016)
This thesis describes studies about the use of azido vinylesters in the development of new selective synthetic processes for the obtainment of tetrasubstituted pyrroles, first fused to a pyridazinone ring, generating pyrrolo[3,4-d]pyridazinones and, second, involving organometallic substituents. It was explored the reaction regioselectivity induced by the presence of certain substituents from the azido vinylesters moiety, and the use of alternative methodologies – such as cascade reactions and microwave irradiation – in the generation of new synthetic procedures, faster, with fewer steps and without the use of catalysts. Initially, we designed the starting materials for the cycloaddition reactions [3+2], resulting in a series of azido vinylesters aril/heteroaryl/metallocenyl substituted, obtained in good yields by Knoevenagel condensation reaction between various aldehydes and methyl azidoacetate. Subsequently, we conducted evaluations on the tetrasubstituted pyrroles regioisomers formation, by cycloaddition reaction between substituted methyl azidoacrylates and 1,3- dicarbonyl compounds and analogous, symmetrical and non-symmetrical, noting that for the aryl/heteroaryl substituted azido vinylesters were obtained pyrroles with only one substitution pattern. Posteriorly, we developed a new methodology for the pyrrolo[3,4-d]pyridazinones formation through a one pot procedure and using a cascade reactions protocol, starting with azido vinylesters and diketones for the in situ generation of the corresponding pyrroles and, after reaction with substituted hydrazines, were synthesized the novel pyrrolo[3,4- d]pyridazinones. In continuation, we studied the chemical behavior of substrates containing an organometallic group for the generation of a novel series of ferrocenyl substituted pyrroles, and in adaptation to the specific characteristics of the organometallic, it was developed a new methodology using a microwave irradiation process, dramatically reducing the reaction time. Also, it was observed the peculiarity of the ferrocenyl moiety, which has acted as a radical ix catalyst in the regioinversion of pyrroles, inverting the substituents positions 2 and 3, differently of the previous results for the synthesis of pyrrolo[3,4-d]pyridazinones. Finally, it was performed the structural characterization of the new compounds by combined techniques of ¹H , ¹³C {¹H}, NMR Spectroscopy, Gas Chromatography coupled to Mass Spectrometry (GC-MS), Liquid Chromatography coupled to Mass Spectrometry (LCESI- MS/MS), Infrared Spectroscopy (IR) and X-Ray Diffraction.